Endemicity of Dengue with Density Figure and Maya Index in Bengkulu City, Indonesia - Triana, Dessy; Foresta Valentine Gunasari, Lala; Helmiyetti, Helmiyetti; Martini, Martini; Suwondo, Ari; Sofro, Muchlis A. U.; Haniyah, Miftahul; Andini, Meilia (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: One of the factors contributing to dengue’s endemicity is the density of the dengue vector, namely, Aedes aegypti as the primary vector and Aedes albopictus as the secondary vector. Bentiring and Kandang Limun villages are high endemic areas of dengue. AIM: This study aimed to determine the relationship between dengue endemicity and density figure (DF) and Maya index (MI) in Bentiring and Kandang Limun villages, Bengkulu city. METHODS: This study used a cross-sectional design. The sampling technique used proportionate stratified sampling. The sampling refers to the guidelines for dengue entomology surveys according to the WHO 1999 criteria. A total of 400 ovitraps were installed, 200 ovitraps inside the house and 200 ovitraps outside the house. RESULTS: The results showed that Bentiring and Kandang Limun villages had a high risk of dengue transmission based on entomological parameters, namely, ovitrap index (OI) 56% and 55% (DF 6), house index (HI) 45% and 44% (DF 6), container index (CI) 23% and 23% (DF 6), and BI 96% and 120% (DF 7 and 8). The areas have a high risk of dengue transmission based on the MI 71% and 76%, respectively. There is a relationship between dengue endemicity and entomological index in Bentiring and Kandang Limun villages, Bengkulu city, with a significance value (p = 0.000) and a powerful correlation (r = 1.000). CONCLUSION: There is a relationship between dengue endemicity and the MI in Bentiring village and Kandang Limun village, Bengkulu city, with a significance value (p = 0.014 and 0.058) and a powerful correlation (r = 0.920 and r = 1.000), respectively. The entomological index and DF are predictors for dengue prevention and control environment to minimize mosquito breeding sites and reduce disease transmission.